PASting together the mammalian clock. - Whitmore, D.; Sassone-Corsi, P.; Foulkes, N.S. (Current Opinion in Neurobiology, 1998)
Over the past year, the first components of the mammalian clock have been identified; Clock, bmal1 and three homologs of Drosophila period have been cloned, all of which encode PAS proteins. Expression of the mammalian period gene oscillates in many tissues in vivo and in immortalized cell cultures in vitro. Now, can we say that every cell has a circadian clock?